How will the career change as Gen Z flourishes? - Ami Pujiwati; Any Meilani; Farida Iriani; Zulkifli Sultan; Etty Susanty (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
The focus of this study is to examine the role of psychological contracts and thriving at work in shaping career engagement, as well as to identify the mediating mechanism between these two variables. A quantitative approach was used with a two-stage data collection technique (time-lagged design) to reduce common method bias. The research sample consisted of 395 respondents aged 20–25 years who are employed in both public and private sectors. The analysis technique used was Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results show that thriving at work and psychological contract fulfillment significantly influence career engagement. Thriving at work has the strongest influence. Additionally, thriving at work was proven to mediate the relationship between psychological contract fulfillment and career engagement. These findings affirm the importance of a work environment that supports learning and self-development in maintaining the engagement and retention of young talent from Generation Z.